2008
DOI: 10.1542/peds.2007-0447
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Multiple Social Risks on Children's Health

Abstract: Multiple social risk factors have a cumulative effect on parent-reported child health status across physical and socioemotional domains, demonstrating a very strong risk gradient effect. These findings emphasize the importance of addressing multiple levels of social risk to achieve improvements in child health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
155
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(173 citation statements)
references
References 52 publications
(29 reference statements)
10
155
0
3
Order By: Relevance
“…The Rochester Longitudinal Study assessed 10 risks and found that children with eight or more risks had rates of poor academic performance that were seven times greater than for children with zero to three risks (78). Subsequent studies support the view that the number of adversities in children's environment affects their healthy development independent of the occurrence of any individual adverse exposure (79)(80)(81).…”
Section: Increasing Complexitymentioning
confidence: 76%
“…The Rochester Longitudinal Study assessed 10 risks and found that children with eight or more risks had rates of poor academic performance that were seven times greater than for children with zero to three risks (78). Subsequent studies support the view that the number of adversities in children's environment affects their healthy development independent of the occurrence of any individual adverse exposure (79)(80)(81).…”
Section: Increasing Complexitymentioning
confidence: 76%
“…They were apt to reside in poor-quality housing, live in neighborhoods with comparatively high crime rates, lack access to health care, and generally have more stressful and less healthful lives . Although the cumulative effects on their health and wellbeing of continued exposure to a mixture of chemical and non-chemical (e.g., psychosocial) stressors is unknown, the potential threat is both real and immediate (Morello-Frosch and Shenassa, 2006;Sexton et al, 2006;Larson et al, 2009;Sexton and Linder, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Preterm infants from disadvantaged backgrounds may be especially vulnerable to such outcomes because of factors such as inadequate social support, financial strain, and poorer access to health care services. 2 Home visiting is 1 strategy to improve a range of maternal-child health outcomes, including preterm birth, in highrisk populations. Currently, anestimated 400 publicly and privately funded home visiting programs provide services for at least 500 000 families in the United States, 3 and an investment of federal funding in this intervention has been made through the Patient Protection and Affordable Care Act (PPACA) to expand and implement programs.…”
mentioning
confidence: 99%